2022
DOI: 10.1186/s12889-022-12950-2
|View full text |Cite
|
Sign up to set email alerts
|

Ethical challenges and moral distress among field epidemiologists

Abstract: Background As ‘disease detectives’ and directors of public health programs, field epidemiologists play essential roles in protecting public health. Although ethical issues receive considerable attention in medical and research settings, less is known about ethical challenges faced by field epidemiologists in public health programs. Similarly, little is known about moral distress among field epidemiologists, i.e., situations in which they are constrained from acting on what they know to be moral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“… 26 The inability to be transparent was a theme Cooke et al found associated with moral distress in epidemiologists. 16 Our results replicated this, and suggest that it is not just the withholding of information, but the active communication of untruthful or misleading information, that can cause moral distress in the public health profession at large. This could be a problem inherent to public health communication, wherever its ultimate goal is to change people’s behavior, as there could be a temptation to simplify or exaggerate the facts in order to achieve that goal.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“… 26 The inability to be transparent was a theme Cooke et al found associated with moral distress in epidemiologists. 16 Our results replicated this, and suggest that it is not just the withholding of information, but the active communication of untruthful or misleading information, that can cause moral distress in the public health profession at large. This could be a problem inherent to public health communication, wherever its ultimate goal is to change people’s behavior, as there could be a temptation to simplify or exaggerate the facts in order to achieve that goal.…”
Section: Discussionsupporting
confidence: 74%
“… 26 Our finding that conflicts between the pursuit of health and the pursuit of other goods (2Ai) were a major driver of this distress, echoes a subtheme of Cooke et al . 16 This kind of moral conflict may be difficult to avoid, since its resolution will often necessarily fall beyond the remit of public health staff, who are professionally bound to prioritize the pursuit of health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One qualitative study of Australian and Canadian health promotion practitioners retrospectively identified moral distress themes from interview transcripts, and an international survey of field epidemiologists found that 91% reported work-related moral distress, with 26% experiencing it ‘frequently’ or ‘always’. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%